Le traitement de la différence à l’école. Deux cas : adolescence et diversité culturelle - Geneviève Zoïa (Recherches en Éducation)
This article discusses the place of diversity education and treatment of ethnocultural differences trough the teacher training in France. Two areas of otherness are addressed: youth culture (Hersent, 2003) and cultural backgrounds. The ethnographic material consists of informal and comprehensive interviews with students and teachers, and derived from experience of responsibility for common training under Masters of the teacher training collège (ESPE). That is why data is collected from students of all disciplines. We show that schools are part of permanent confrontation standards, together with a rather political legitimation and recognition, that comes necessarily meet the training aera.